EMPIRICAL ANALYSIS OF APPROACHES TO THE DEVELOPMENT OF ECONOMIC INFRASTRUCTURES BASED ON PUBLIC-PRIVATE PARTNERSHIP (World Economics and Finance Bulletin, 2025)
This article analyzes the development of public-private partnership (PPP) projects in the Republic of Uzbekistan and their significant role in modernizing the country's infrastructure. In particular, the collaboration with international financial institutions, such as the Asian Development Bank, the International Finance Corporation, and the World Bank, in implementing PPP projects is highlighted. The article addresses the objectives of PPP projects, including enhancing project quality, ensuring sustainability, and creating opportunities for effective investments. It also focuses on issues such as contractor selection, competition in the procurement process, and risk management. The effectiveness of public-private partnerships, including the participation of the private sector in infrastructure projects and the implementation of their financing in developing countries, is analyzed.